Political altruism of water sharing - Bhaduri, Anik; Barbier, Bruno (Walter de Gruyter GmbH, 2008)
In the paper, using a political altruism model, we make an attempt to explain why an upstream country might agree to a treaty that recognizes and enforces the water claims of a downstream country. In a natural extension of the standard economic model, it is possible to explain the above phenomena, by allowing for altruism between countries. The altruistic concerns of the countries are dependent on other country's willingness to have a good political relationship. If both the countries maintain favorable political relations with one another, then the upstream country will care about the impacts of its water diversion on the downstream country's welfare. The paper also illustrates the case of water sharing of the Ganges River between India and Bangladesh. The Ganges River, like many other rivers in the world, ignores political boundaries. In Bangladesh, the final downstream country along the Ganges, freshwater availability depends on the share of water diverted by the upstream country, India. For decades, India and Bangladesh failed to resolve the water-sharing issues of the Ganges River. However, in 1996, both India and Bangladesh signed a major new agreement on water sharing (Ganges River Treaty) in an effort to resolve the dispute. Using the political altruism model developed in the paper, we examine why despite needing more water than is available under the treaty, India has adapted to shortages instead of resorting to conflict with Bangladesh.